Reduction of Postoperative Hip Arthroscopy Pain With an Ultrasound-Guided Fascia Iliaca Block: A Prospective Randomized Controlled Trial. Issue 3 (March 2020) - Glomset, John L.; Kim, Eugene; Tokish, John M.; Renfro, Suzanne D.; Seckel, Tyler B.; Adams, Kyle J.; Folk, Jason
Background: Ultrasound-guided fascia iliaca blocks have been used for pain control after hip arthroscopy. There is little evidence regarding their effectiveness in comparison with other pain control modalities in patients who have undergone hip arthroscopy. Purpose: To compare the efficacy of ultrasound-guided fascia iliac block with intra-articular ropivacaine in controlling pain after hip arthroscopy. Study Design: Randomized controlled trial; Level of evidence, 2. Methods: Between 2015 and 2017, patients (N = 95) undergoing hip arthroscopy were randomly assigned to 2 groups. The first group received an ultrasound-guided fascia iliaca block with 50 to 60 mL of 0.35% ropivacaine. The second group received an intra-articular injection of 20 mL of 0.5% ropivacaine at the completion of the surgical case. Primary outcomes were postoperative pain scores in the recovery room; at postanesthesia care unit (PACU) discharge; and at 2 weeks, 6 weeks, and 3 months. Secondary outcomes included intraoperative and PACU narcotic usage (converted to morphine equivalent use) as well as readmission rates, PACU recovery time, and postoperative nausea and vomiting. Results: Postoperative pain across all points did not significantly differ between the groups. Intraoperative and PACU narcotics did not differ significantly between the groups. Readmission rates, PACU recovery time, and postoperative nausea and vomiting did not significantly differ between the groups. There were no associated complications in either group. Conclusion: Ultrasound-guided fascia iliaca block for hip arthroscopy had no clinical advantage when compared with onetime intra-articular ropivacaine injection. Registration: NCT02365961 (ClinicalTrials.gov identifier).